Thermal Comfort in Kobuang Limo House: Evaluating Tropical Architectural Elements - Mulfakli; Zulherman; Fuadi, Al Busyra (Departement of Architecture, Universitas Islam Indonesia, 2025)
This study investigates the effectiveness of tropical architectural elements in maintaining thermal comfort in the Kobuang Limo House, a traditional Malay dwelling in Riau, Indonesia. Employing an embedded mixed-method approach, the research integrates field measurements and interviews with climate-based simulations. Thermal comfort was evaluated using Effective Temperature (ET), based on SNI 03-6572-2001, incorporating air temperature, humidity, and wind speed. A three-day field measurement in December 2024 showed that the hipped roof, singap ventilation, wall openings, and raised floors contributed to passive cooling, although corrugated zinc roofing increased indoor temperatures during the day. To extend the analysis over an annual cycle, statistical monthly climate data from BMKG were used in combination with deviation-based correction factors to simulate indoor conditions. Results indicate that ET values remained within the optimal to slightly warm comfort categories throughout the year, with peak values observed in bedrooms and kitchens during the dry season. The findings emphasize the adaptive performance of tropical architectural design and suggest improvements in insulation and cross-ventilation strategies.